Տայքում և Կղարջքում Բագրատունիների վրացական ճյուղի իշխանության հաստատման թվականի շուրջ - Լիանա Նազարյան (ՀՀ ԳԱԱ հրատ.)
В 774–775 гг., после поражения в битве Багреванда, понесенного от арабов, одна ветвь Багратидов утвердилась в Тайке и соседнем Кхарджке, создав линию грузинских Багратидов. After the defeat in the Bagrevand battle of 774–775, a branch of the Bagratuni settled down in Tayk and the neighbouring Kgharjk laying the foundation of the Georgian Bagratuni.
Keywords: History; Medieval History; D History